The Demand for Insurance: Expected Utility Theory from a Gain Perspective - John A. Nyman (University of Minnesota, Center for Economic Research, 2001)
Expected utility theory holds that the demand for insurance is a demand for certainty, because under the conventional specification of the theory, it appears as if buyers of insurance prefer certain losses to actuarially equivalent uncertain ones. Empirical studies, however, show that individuals actually prefer uncertain losses to actuarially equivalent certain ones. This paper attempts to reconcile expected utility theory with this empirical evidence by suggesting that insurance is demanded to obtain an income payoff in the Abad@ state. This specification is mathematically equivalent to the conventional specification and consistent with this and other empirical evidence, but it implies that the demand for insurance has nothing to do with demand for certainty.
Keywords: 330; Versicherung; Nachfrage; Erwartungsnutzen; Versicherungsökonomik; Theorie